A Day in the Life of a Coach - Bowman-Kruhm, Mary and Claudine G. Wirths (New York The Rosen Publishing Group, 1999)
Describes some of the activities involved in Coach Jackson's work as an elementary school gym teacher and a high school football coach.
Keywords: Football coaches; Occupations